Rewolucja „Solidarności” w stolicy polskiej piosenki (1980–1989). Postawy i rola społeczna twórców w czasach przełomu na przykładzie Opola - Bereszyński, Zbigniew (Pamięć i Sprawiedliwość, 2014)
The revolutionary social and political changes initiated in the summer of 1980, related to the birth of and activities conducted by the Solidarity movement, took place mainly because of the social mobilization of workers. The direction and nature of these changes were also determined – albeit not necessarily in an active manner – by the attitude of other social structures, particularly the creative circles. Opole, the city regarded since 1963 in terms of an informal capital of the Polish song – is a good example. The 19th National Contest of the Polish Song, held from 25 until 28 June 1981, became a legend. The song “Let Poland be Poland”, performed to the general public at this festival, became an unofficial anthem of the Solidarity revolution. For political reasons, the festival organizers could not interfere in the course of the festival. The censorship intervention proved unsuccessful, as well. The activity of TSA, a rock group set up in Opole, was also a major phenomenon on a national scale. The group’s songs constituted a certain attempt at escaping from the greyness and hopelessness of everyday life in communist Poland. Somehow shadowed by these phenomena were local facts connected with individual attitudes of representatives of the Opole creative circles towards the revolutionary changes taking place in Poland’s social and political life. These facts, however, are also significant in the context of illustrating the social realities of the 1980s. A vast majority of artists from Opole was not actively engaged in the endeavours of the opposition forces, but – at the same time – they would neither attack the opposition nor side with the authorities. Cases of active involvement in the activities undertaken by one or the other side of the political barricade were quite rare. The longstanding opposition activity of the Opole actor Tadeusz Żyliński calls for special attention. This man is an example through which one can see quite clearly how much could be done by politically active artists after August 1980. Unfortunately, only a small part of the Opole creative circles was interested in such opportunities. Political passivity, coupled with efforts aimed at fulfilling one’s own personal and professional ambitions, were definitely more prevailing. Everyday social and political reality of the 1980s in Poland was a far cry from the idealistic views on the social mission of our intelligentsia.